Black carbon and size-segregated elemental carbon, organic carbon compositions in a megacity: a case study for Istanbul - AKKOYUNLU, BÜLENT OKTAY (SPRINGER, 2020)
In this study, black carbon (BC), particulate matter (PM), nitrogen oxides (NOx), and sulphur dioxide (SO2) were monitored between May 2019 and February 2020. During this sampling period, size-segregated particle samples were collected by a high-volume cascade impactor, once a week. Elemental carbon (EC) and organic carbon (OC) were investigated on the size-segregated particles. The study was carried out at Esenler district of Istanbul. Main sources in the vicinity of the sampling area are Central Coach Station of Istanbul, residential buildings, small-scale industrial facilities, and O-1 and O-2 highway connection. The average BC concentration was 2763 +/- 1974 ng/m(3). PM10 and PM2.5 concentrations were 38.2 +/- 17.4 and 21.5 +/- 12.4 mu g/m(3), respectively. BC comprised 12.8% and 7.2% of PM2.5 and PM10, respectively. Diurnal variation of BC had a similar trend with NO2 concentrations, which showed peak concentrations during rush hours. BC had high Pearson correlation coefficients with NO, NO2, and PM2.5. The geographical position of possible emission sources was estimated through conditional probability function. The Central Coach Station of Istanbul had the highest geographical possibility for BC sources. EC and OC exhibited bimodal size distribution. The coarse mode peak was at 0.95-1.5-mu m size bin for OC, whilst it was at 1.5-3-mu m size bin for EC. Since EC and BC exhibit the same origin with different measurement principles, we concluded that resuspension of road dust also contributed ambient BC concentrations.
Keywords: Black carbon; OC-EC; Aerosol size distribution; Megacity; AIR-POLLUTION; PARTICULATE MATTER; AEROSOLS; TRENDS; PM2.5; PLAIN